Monitoring of Conjunctival Microcirculation Reflects Sublingual Microcirculation in Ovine Septic and Hemorrhagic Shock. Issue 4 (April 2019) - Hessler, Michael; Arnemann, Philip-Helge; Zamit, Frédéric; Seidel, Laura; Kampmeier, Tim-Gerald; Kathöfer, Ulrich; Alnawaiseh, Maged; Tchaichian, Saman; Rehberg, Sebastian; Ertmer, Christian
ABSTRACT: Introduction: The conjunctival region may serve as an alternative site for microcirculatory measurements. The present study was performed to investigate the correlation of sublingual and conjunctival microcirculation in ovine models of septic and hemorrhagic shock. Methods: Septic shock was induced in 10 sheep by inoculation of feces into the peritoneal cavity until mean arterial pressure (MAP) was <60 mm Hg and arterial lactate level was ≥1.8 mmol· L −1 . In another 10 sheep, hemorrhagic shock was induced by stepwise blood withdrawal of 3×10 mL·kg −1 . Systemic hemodynamics and parameters of blood gas analysis were analyzed. Conjunctival and sublingual microcirculation were monitored and analyzed according to current recommendations. Parameters were measured at baseline and at shock time. Results: Septic shock resulted in a significant drop in MAP and cardiac index (CI), and an increase in arterial lactate levels. While the total vessel density (TVD) in the sublingual microcirculation was relatively well maintained, the perfused vessel density (PVD) and the microvascular flow index (MFI) were significantly reduced in septic shock. Hemorrhagic shock reduced MAP and CI, and increased arterial lactate levels. TVD was relatively unchanged in hemorrhagic shock, while PVD and MFI were significantly decreased. The conjunctival microcirculation showed similar changes to the sublingual microcirculation in both models. Conclusions: The findings of the current study support the proposed use of the conjunctiva as an alternative site for microcirculatory monitoring in hemorrhagic and septic shock. Further studies should focus on the impact of therapy and the loss of correlation between the different microcirculatory regions in advanced shock. Abstract : Supplemental Digital Content is available in the text